The Emergence and Impact of Educational Pavilions in the History of World Exhibitions in the 19th and Early 20th Centuries, with Particular Regard to Hungarian Participation - Albrecht, Zsófia (Per Aspera ad Astra, 2025)
After the success of the first international world exhibition held in London in 1851, it became widely accepted that events like this could serve multiple purposes – not only were they economically beneficial, but they also helped build a nation's image and provided an excellent opportunity for the exchange and transfer of cultural knowledge. During world exhibitions, people could "travel around" the world, getting to know countries and nations without having to cross oceans and continents. The theme of the 1873 Vienna world’s fair was education, with a dedicated exhibition pavilion. The theme of education also played a prominent role in subsequent world exhibitions, providing an opportunity for various cultural and educational institutions to introduce themselves and showcase the work of their students (the latter was particularly important in the case of art schools). The study provides an overview of the initial findings of a current research into the history of world exhibitions (focusing on the period 1851–1900) with regard to the educational sections, and later pavilions at world’s fairs (with a special focus on Hungarian participation), using sources (official documents, photos) that haven't been published in Hungarian literature before.